Prooxidant and antioxidant properties of human serum ultrafiltrates toward LDL: important role of uric acid - Rebecca A. Patterson; Elizabeth T.M. Horsley; David S. Leake (Journal of Lipid Research, 2003)
Oxidized LDL is present within atherosclerotic lesions, demonstrating a failure of antioxidant protection. A normal human serum ultrafiltrate of Mr below 500 was prepared as a model for the low Mr components of interstitial fluid, and its effects on LDL oxidation were investigated. The ultrafiltrate (0.3%, v/v) was a potent antioxidant for native LDL, but was a strong prooxidant for mildly oxidized LDL when copper, but not a water-soluble azo initiator, was used to oxidize LDL. Adding a lipid hydroperoxide to native LDL induced the antioxidant to prooxidant switch of the ultrafiltrate. Uric acid was identified, using uricase and add-back experiments, as both the major antioxidant and prooxidant within the ultrafiltrate for LDL. The ultrafiltrate or uric acid rapidly reduced Cu2+ to Cu+. The reduction of Cu2+ to Cu+ may help to explain both the antioxidant and prooxidant effects observed. The decreased concentration of Cu2+ would inhibit tocopherol-mediated peroxidation in native LDL, and the generation of Cu+ would promote the rapid breakdown of lipid hydroperoxides in mildly oxidized LDL into lipid radicals. The net effect of the low Mr serum components would therefore depend on the preexisting levels of lipid hydroperoxides in LDL.These findings may help to explain why LDL oxidation occurs in atherosclerotic lesions in the presence of compounds that are usually considered to be antioxidants.